MENAKAR MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM: STRATEGI DAN DAMPAK - M. Nasihuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Indonesia is a Muslim-majority country with extraordinary cultural and religious diversity. The application of religious moderation is essential toining a balance between religious traditions and modern social dynamics. This study aims to explore strategies for the application of religious moderation to the Islamic education system in Indonesia, as well as to assess its impact on student understanding and behavior and to enhance understanding of how to integrate religious equality into the education system using a qualitative approach. It is expected that this research will significantly contribute to promoting peace and tolerance through education and preparing Indonesians for the challenges of globalization and increasingly complex pluralism.